Assessment of Smoking Behaviors, Attitudes, and Health Perceptions: A Comprehensive Survey - Pushpendra Singh; Radhika Vaidya (Oral Sphere Journal of Dental and Health Sciences, 2025)
Introduction: Tobacco consumption is a leading cause of death globally, with significant impacts on public health. In India, tobacco use contributes to a substantial loss in GDP and is a major risk factor for various diseases. This study investigates smoking behaviors, attitudes, and health perceptions to understand the factors influencing smoking and attempts to quit. To assess smoking behavior, health perceptions, attitudes towards smoking, and awareness of smoking-related risks in participants, along with the relationship between smoking habits and health. Methods: The study used a voluntary online survey, collecting data on smoking frequency, age of initiation, awareness of smoking risks, and the impact of smoking on oral and general health. The survey also examined participants’ attempts to quit smoking and their motivations for smoking. Methodology: Data analysis involved descriptive statistics and Chi-square tests to evaluate associations between smoking behaviors and health conditions. Results: The majority of respondents were non-smokers (73.6%), with most smokers starting in early adulthood. Stress was the primary motivator for smoking among smokers. Awareness of health risks was high (88.7%), but quitting attempts were limited, with a significant number of smokers making fewer than five attempts to quit. Oral health problems were reported by a small number of smokers, with most respondents reporting no issues. Conclusion: While there is a high level of awareness of the health risks associated with smoking, efforts to quit are limited. Interventions targeting stress and habit-breaking strategies, as well as more inclusive research covering smokeless tobacco, are needed.